The Determinants of Capital Structure: Some Evidence from Banks - Florian Heider; Reint E. Gropp (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
This paper documents that standard cross-sectional determinants of firm leverage also apply to the capital structure of large banks in the United States and Europe. We find a remarkable consistency in sign, significance and economic magnitude. Like non-financial firms, banks appear to have stable capital structures at levels that are specific to each individual bank. The results suggest that capital requirements may only be of second-order importance for banks? capital structures and confirm the robustness of current corporate finance findings in a holdout sample of banks.
Keywords: G32; G21; 330; capital structure; corporate finance; leverage; bank capital; banking regulation; Bank; Kapitalstruktur; Vergleich; Industrie; Bankenpolitik; EU-Staaten; USA